BODY TEMPERATURE OF BARREN GROUND CARIBOU - McEwan, E. H.; Wood, A. J.; Nordan, H. C. (Canadian Journal of Zoology, 1965)
Rectal temperatures were recorded for barren ground caribou during their first 100 days of life. The normal rectal temperature of caribou was found to be 39 ± 0.78 °C. Temperature elevations of 2.2 °C occurred as a result of activity. The practical implications of these observations are discussed.